Precipitation of Xylan from Agricultural Waste Using Acid and Alcohol to produce Bio-Polymer Film (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Xylan from natural sources such as agricultural waste can be used to produce biopolymer packaging films and reduce the use up of petrochemical film. In this study, three different agricultural wastes (oil palm frond, sugarcane bagasse and corn stover) were used to extract xylan by using various alkaline and acidic solvents. From the analysis of the composition of oil palm fronds, it was found that oil palm frond contains (%) 30.8 ± 0.4 glucan, 19.3 ± 0.3 xylan and 18.4± 0.8 lignin.  The percentage of extraction of xylan with sodium hydroxide is higher than sulfuric acid and dimethyl sulfoxide. Xylan extracted with dimethyl sulfoxide contains acetyl qualifiers and is suitable for producing carboxymethyl xylan.  For xylan deposition, the use of a high concentration of ethanol gave a high xylan precipitation. Finally, the film with sorbitol as a plasticizing material showed low water absorption and high tensile strength of 4,855 gs-1m-1 Pa and 26 Mpa respectively.
Keywords: Xylan; Bio-Polimer film; Kenaf; Oil Palm Frond; Precipitation